Design and development of a slider-crank actuated knee exoskeleton with optimized motion controller - Md Ghazaly, Mariam; Nai, Jun An; Law, Hin Kwee; Abdullah, Zulkeflee; Hasim, Norhaslinda; Halim, Isa; Zainal, Nasharuddin (International Islamic University Malaysia, 2024)
The rising incidence of injuries and neurological disorders has highlighted the critical need for accessible and affordable rehabilitation solutions. In response to this demand, robotic exoskeletons have become a popular option for rehabilitation. However, current rehabilitation exoskeletons are generally expensive due to the high force of the actuators used, i.e., electric motors. Therefore, the availability is limited to patients who can afford to pay for physiotherapy using these robotic exoskeletons. Because of the demand for high force, the exoskeleton is heavy, impacting patient safety. In response to these challenges, the main contribution of this study is to develop a lightweight lower-body rehabilitation exoskeleton with sufficient force while maintaining a fast response time and precise motion control for rehabilitation purposes. In this research, a lower body knee joint rehabilitation exoskeleton prototype implementing a slider-crank mechanism was meticulously designed and optimized using Finite Element Analysis (FEA) via SolidWorks software. After optimising the design, the lower body exoskeleton (LBE) was fabricated and assembled. Next, the LBE system was characterized to understand its non-linear behaviour, as the LBE uses a double-acting pneumatic cylinder that is known to exhibit non-linear behaviour. To further analyse the effectiveness of LBE for rehabilitation, a ProportionalIntegral-Derivative (PID) controller was adopted for its simplicity in controlling the exoskeleton's angular motions. Excellent results were obtained using a PID controller at the angular displacement of 75ᵒ, with a 96.5% reduction in overshoot (OS%), a 92.9% decrease in steady-state error (Ess), a 3.2% reduction of rise time (Tr), and a minimal 0.006% reduction in settling time (Ts). These findings indicate that the LBE with the slider-crank mechanism is a promising device, particularly for knee joint rehabilitation, and that it can be applied to other rehabilitation applications that require a lightweight design and high force application.